Cryptococcal infection in lung transplant recipients: A 5‐year retrospective review at an Australian transplant center. Issue 6 (31st August 2018) - Sohail, Asma; Smibert, Olivia C.; Snell, Greg; Paraskeva, Miranda; Jenney, Adam
Abstract: Cryptococcosis is a common invasive fungal infection (IFI) in solid organ transplant (SOT) recipients. Little is known about cryptococcosis in lung transplant (LTx) recipients despite having one of the highest risks of infection. The aim of this study was to describe demographic and clinical features of cryptococcal infection in LTx recipients. We performed a retrospective, observational study of cryptococcal infection in LTx recipients at The Alfred Hospital in Melbourne, Australia, from 2012 to 2017. A total of 11 cases were identified. Seven patients (64%) were male and the median age was 54.7 years (range 34‐69 years). Diagnosis occurred at a median of 233 days (range 1‐3650 days) post‐transplant. Nine patients (82%) had isolated pulmonary infection of whom 7 (78%) were asymptomatic. All were treated with oral antifungal therapy and 1 required surgical resection of infected lung. Two patients (18%) had disseminated infection; 1 with pulmonary and central nervous system (CNS) infection and 1 with isolated CNS infection. Both patients presented with headache and brain imaging demonstrated cerebral edema, myelinosis, and leptomeningeal enhancement. One of these patients died. This study highlights the fact that cryptococcal infection should remain a consideration in asymptomatic LTx recipients, especially in the presence of non‐specific nodules on chest imaging, and that the presence of headache in these patients requires urgent investigation for CNS infection.